PERAN PENGUSAHA DAN PENGELOLA PASAR DALAM PENGEMBANGAN PASAR TRADISIONAL DI SIDOARJO - Firda Febrianti, Putri; Helmi; Tri Kuncoro, M. Firdaus; Irawati, Dyan (Universitas 17 Agustus 1945 Semarang, 2024)
Traditional markets in Sidoarjo, like in many places in Indonesia, play an important role in the local economy and community life. However, the challenges of modernization and competition with modern markets have threatened the sustainability of these traditional markets. The role of entrepreneurs and market managers is key in developing traditional markets in Sidoarjo. This research aims to analyze the role of entrepreneurs and market managers in developing traditional markets in Sidoarjo. The research method used is a qualitative study with data collection techniques through in-depth interviews and direct observation in the field. The research results show that entrepreneurs have a strategic role in increasing the competitiveness of traditional markets through product innovation, promotion and improving service quality. Meanwhile, market managers play an important role in organizing market governance, ensuring cleanliness, safety and comfort of visitors, as well as facilitating cooperation between sellers. By actively involving entrepreneurs and market managers in the development process, traditional markets in Sidoarjo can face the challenges of modernization and increase their attractiveness for local communities and tourists. In conclusion, close collaboration between entrepreneurs and market managers is needed to ensure the sustainability and progress of traditional markets in Sidoarjo.